2015
DOI: 10.1007/s10439-015-1416-2
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Collagen Matrix Density Effect on Endothelial Sprout Formation Using Experimental and Computational Approaches

Abstract: A thorough understanding of determining factors in angiogenesis is a necessary step to control the development of new blood vessels. Extracellular matrix density is known to have a significant influence on cellular behaviors and consequently can regulate vessel formation. The utilization of experimental platforms in combination with numerical models can be a powerful method to explore the mechanisms of new capillary sprout formation. In this study, using an integrative method, the interplay between the matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 66 publications
2
39
0
1
Order By: Relevance
“…With this corresponding matrix density index obtained, the angiogenesis process, that is the migration of endothelial cells, is simulated mimicking different collagen density effect. Shamloo et al confirmed their previous model predictions on endothelial sprout formation morphology under different ECM matrix. Recent studies also consider the effect of MMP and the nucleus compartments in cell migration using cellular Potts models.…”
Section: Cellular Computational Models In Cell Migrationsupporting
confidence: 66%
See 2 more Smart Citations
“…With this corresponding matrix density index obtained, the angiogenesis process, that is the migration of endothelial cells, is simulated mimicking different collagen density effect. Shamloo et al confirmed their previous model predictions on endothelial sprout formation morphology under different ECM matrix. Recent studies also consider the effect of MMP and the nucleus compartments in cell migration using cellular Potts models.…”
Section: Cellular Computational Models In Cell Migrationsupporting
confidence: 66%
“…The cellular Potts model has addressed multiple cell migration predictions that can be validated by experiments. One of the successes is in predicting endothelial cell migration in angiogenesis . Shamloo et al first used an in silico collagen fibrils model to estimate the corresponding matrix density index used in their model through matching collagen area in microscopic and in silico images under different densities.…”
Section: Cellular Computational Models In Cell Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been reported that collagen sponge scaffolds prepared from porcine and bovine collagen have different structures, only porcine collagen has been investigated for its regenerative effect on the tracheal epithelium. Because the structure of collagen sponge scaffolds is known to affect cell behavior, collagen sponges with various structures have been prepared by modifying crosslinking methods, collagen concentration, and temperature for freezing the collagen solution . However, the concentrations of bovine collagen that are optimal for tracheal epithelial regeneration have never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Because the structure of collagen sponge scaffolds is known to affect cell behavior, collagen sponges with various structures have been prepared by modifying crosslinking methods, collagen concentration, and temperature for freezing the collagen solution. 15 However, the concentrations of bovine collagen that are optimal for tracheal epithelial regeneration have never been reported.…”
Section: Introductionmentioning
confidence: 99%